Predictive Modelling of Kidney Stones Using Clinical Urine and Blood Parameters - Priyamvad Ranjan (International Journal of Intelligent Systems and Applications in Engineering, 2026)
This paper presents a comprehensive machine learning (ML) framework for non-imaging kidney stone prediction from clinical urine and blood parameters. A dataset of 350 patient records with 35 features was processed through a systematic pipeline comprising KNN-based missing value imputation, RobustScaler normalization, and SMOTE class balancing. Eight clinically motivated engineered features — including volume-corrected oxalate and calcium concentrations, pH-uric acid risk index, and a composite clinical risk score — were derived and validated through mutual information feature selection. Nineteen ML models spanning traditional classifiers, tree-based ensembles, and gradient boosting frameworks (XGBoost, LightGBM, CatBoost) were trained and systematically compared. Bayesian hyperparameter optimization via Optuna achieved a cross-validation ROC-AUC of 0.9315 in the Stacking ensemble, while K-Nearest Neighbors attained the best test-set accuracy (80.0%, AUC 0.8435). SHAP-based Explainable AI analysis confirmed alignment between model predictions and established nephrology risk factors. Probability calibration reduced expected calibration error from 0.087 to 0.041, and threshold optimization was employed to maximize clinical sensitivity. The proposed framework demonstrates that rigorous preprocessing, domain-driven feature engineering, and ensemble optimization can yield clinically useful predictive performance from routine laboratory data in moderate-sized patient cohorts.